L’UNESCO et la promotion des politiques scientifiques nationales en Afrique sub-saharienne, 1960-1979 - Davis, Charles (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1983)
In the last two decades many African states established science policy institutions inspired, directly or indirectly, by the promotional activities of UNESCO. This paper examines certain aspects of UNESCO's science policy assistance activities in Africa and describes the science policy devices that are proposed to African states inapproximately 45 mission reports. While the principal function of science policy is supposed to be to increase the utility of national scientific and technical resources, science policy assistance takes place within contexts that lend other kinds of significance to it. Three factors that have contributed to the expansion of UNESCO-promoted science policy bodies in Africa are discussed: entrepreneurial initiatives on the part of UNESCO, the volontarist-managerial approach to domestic political decision-making offered by the UNESCO science policy paradigm, and assistance relations between donors and African clients.